A WEB APP TO GENERATE AND DISSEMINATE NEW KNOWLEDGE ON URBAN GREEN SPACE QUALITIES AND THEIR ACCESSIBILITY - R. Hecht; M. Artmann; P. Brzoska; D. Burghardt; S. Cakir; A. Dunkel; M. Gröbe; M. Gugulica; K. Krellenberg; K. Krellenberg; N. Kreutzarek; S. Lautenbach; et al. (ISPRS Annals of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2021)
Urban green spaces (UGSs) can provide important ecosystem services for citizens and their well-being. To make use of these services according to UGS user demands, urban residents, tourists, and city administrations should know where UGSs are located, what qualities they have and how to reach them on convenient routes. This paper presents a novel digital infrastructure which combines and fuses different data to map UGSs and their qualities, and makes this information available in a web app. The interactive information service of the app aims to support citizens to explore and search for suitable UGSs and to provide routing options to reach them based on their preferences. Via implicit and explicit feedback functions included in the app, further information on UGS users' preferences can be collected to enhance the overall knowledge basis, while respecting data privacy issues. The underlying data base consists primarily of open and volunteered geographic data, which allows for transferability to other cities. This paper describes the system design, its back-end and front-end components, as well as the process of development and deployment of the system in two pilot cities. Preliminary results of the piloting in the two cities are presented, focusing on user preferences for UGSs searches. The added value of the web app for city residents and the role of the newly gained knowledge for urban planning is discussed and reflected upon.